Women's Patterns of Talk in The Third Wife Movie Script (Application in Family Environment) - Gultom, Eva; Sartika, Dewi (ENJEL: English Journal of Education and Literature, 2023)
In this study, Deborah Tannen's theory is used to explain how women talk in The Third Wife. To examine the data, a qualitative descriptive method was adopted in this study. The Third Wife script serves as the main source of data for this study. From the analysis, the researchers notified there are three ways to demonstrate the women's speaking patterns in context, notably those related to mother dynamics, connection and control, and metamessage. These are present in polygamous homes, particularly in the context of this film. Nonetheless, there is an exchange of positions in which women fill the void since the absence of a husband figure influences how they interact with one another, as the first wife. This happens because there is a special relationship that is formed between the wives which makes the pattern of talk create itself between them. The lack of a husband figure impacts how they interact with each other, as the first wife (Ha), is in control and holds the most important rank in the family, followed by the second wife (Xuan), and the last one the third wife (May). The status of the family heavily impacts the wives’ talk to each other and the style of their speech. In the family setting of this movie, women with higher status may use more assertive language and dominate conversations.